Myeloid masquerade: Microglial transcriptional signatures in retinal development and disease - Pitts, Kristen M.; Margeta, Milica A. (Frontiers in Cellular Neuroscience, 2023)
Microglia are dynamic guardians of neural tissue and the resident immune cells of the central nervous system. The disease-associated microglial signature (DAM), also known as the microglial neurodegenerative phenotype (MGnD), has gained significant attention in recent years as a fundamental microglial response common to various neurodegenerative disease pathologies. Interestingly, this signature shares many features in common with developmental microglia, suggesting the existence of recycled gene programs which play a role both in early neural circuit formation as well as in response to aging and disease. In addition, recent advances in single cell RNA sequencing have revealed significant heterogeneity within the original DAM signature, with contributions from both yolk sac-derived microglia as well as bone marrow-derived macrophages. In this review, we examine the role of the DAM signature in retinal development and disease, highlighting crosstalk between resident microglia and infiltrating monocytes which may critically contribute to the underlying mechanisms of age-related neurodegeneration.